Estimativas de herdabilidade e correlações genéticas, fenotípicas e ambientais de pesos e ganhos de peso do nascimento ao desmame em bovinos da raça nelore - Rocha, Marco Antonio da (Semina: Ciências Agrárias, 1989)
<!–[if gte mso 9]> Normal 0 21 MicrosoftInternetExplorer4 <![endif]–> <!– /* Font Definitions */ @font-face font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:35.4pt; mso-footer-margin:35.4pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> In order to study the genetic effects upon the characteristics: birth weight (BW); average daily weight gain from birth to weaning (ADWW) and weight at weaning (WW), we examined a sample of cattle at the Estância Nelore, haguagê - PR, The sample is made up of 332 animals of the Nelore race, 177 males and 155 females horned from 1978 to 1981, The model for analysis included the following effects: sire, birth year, animal sex interaction between birth year and animal sex, The character sire was significative (P<0,01) for WW and ADWW, the birth year was significative (P <0,01) for WW and ADWW, the animal sex was significative for the three characteristics (P <0,01), but the interaction between year and sex was not significative. The estimate of heritability for BW, WW and ADWW were respectively: 0,08 Â± 0,10; 0,39 Â± 0,19; 0,32 Â± 0,18 and the estimates of genetic, phenotypic and environmental correlations for BW X WW; BW X ADWW and WW X ADWW were (0,95; 0,25; 0,12); (0,92; 0.18; 0,03) and (0,99; 0,96; 0,95) respectively. These results show that it is possible to obtain a good result based upon the selection for weaning weight or average daily gain from birth to weaning.